2007
DOI: 10.1111/j.1365-2036.2006.03239.x
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide in luminal and fistulizing Crohn's disease resistant to standard therapies

Abstract: SUMMARY BackgroundThalidomide has been shown to be an effective treatment in Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 27 publications
4
53
0
Order By: Relevance
“…Thalidomide abolishes the endogenous overproduction of TNF-a in patients suffering from various different diseases [1, 25-27, 32, 47]. Clinical observations confirmed that the antiinflammatory properties of thalidomide utilized for the treatment of rheumatoid arthritis, inflammatory bowel disease and Crohn's disease are due to the inhibitory effect on TNF-a and/or IL-1 [4,30,37]. Since estrogen deficiency-related osteoporosis is presumably linked to the increased release of proresorptive cytokines (IL-1, IL-6 and TNF-a) [18,21,28,33], one may presume that the alleviation of bone resorption and improvement of bone mechanical properties observed here in ovariectomized rats receiving 15 mg/kg, po thalidomide, were the result of its effect on those cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thalidomide abolishes the endogenous overproduction of TNF-a in patients suffering from various different diseases [1, 25-27, 32, 47]. Clinical observations confirmed that the antiinflammatory properties of thalidomide utilized for the treatment of rheumatoid arthritis, inflammatory bowel disease and Crohn's disease are due to the inhibitory effect on TNF-a and/or IL-1 [4,30,37]. Since estrogen deficiency-related osteoporosis is presumably linked to the increased release of proresorptive cytokines (IL-1, IL-6 and TNF-a) [18,21,28,33], one may presume that the alleviation of bone resorption and improvement of bone mechanical properties observed here in ovariectomized rats receiving 15 mg/kg, po thalidomide, were the result of its effect on those cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Thalidomide has been approved for the treatment of multiple myeloma and erythema nodosum leprosum. Clinical trials are currently being conducted for its use in treating inflammatory diseases, various neoplastic diseases, complications of human immunodeficiency virus infection, chronic graft-versus-host disease and numerous dermatological conditions, among others [1,13,19,23,25,27,29,30,37,44].…”
Section: Introductionmentioning
confidence: 99%
“…For patients with complete short-term response (weeks [4][5][6][7][8][9][10][11][12] and when data were also available beyond week 12, we analysed the percentage of …”
Section: Long-term Efficacymentioning
confidence: 99%
“…In a retrospective study, 7 medical treatment including steroids, antibiotics or amino-salycilate healed fissures in 46% of 52 patients after a median follow-up of 92 months. In two patients with perianal ulcers treated with thalidomide, one achieved clinical response and the other one showed initial improvement with reduction in ulcer size and drainage at 1 year, 10 Ciclosporin treatment healed 70% of perianal ulcers in 20 patients after a median follow-up of 7 months. 11 Regarding topical treatment, 10% metronidazole decreased the Perianal Crohn's Disease Activity Index and anorectal pain in 14 patients at 4 weeks, 12 whereas tacrolimus did not heal ulcers, but led to rapid improvement in terms of depth, surface area and pain in 4 patients after 3 months, 13,14 Local depot methylprednisolone injection also showed some efficacy in treating painful anal Crohn's disease in 5 patients with a follow-up of 12 months.…”
mentioning
confidence: 92%
“…Studies have reported that clinical response at month 3 was 60-75%, with 20-40% patients able to maintain remission [85][86][87][88][89], and about 40% of patients able to stop steroids [85]. In a randomized controlled trial studying the effect of thalidomide on clinical remission in pediatric refractory CD, the mean duration of remission in the thalidomide group was 181.1 weeks, compared to 6.3 weeks in the placebo group (p \ 0.001) [90].…”
Section: Thalidomidementioning
confidence: 99%